An examination of six macroenvironment forces on globalization between 2006 and 2018 - AbdulHafiz, AbdulHafiz Henry James; Talal Alsaif (Archives of Business Research, 2021)
This study looks at the economic, political, environmental, cultural, technological, legal, and ethical macro-environmental forces which impact globalization Pre-2018. Key events are examined as indicators of the state of globalization around the world. The examination of globalization centers on these key events in the United States and Saudi Arabia. The issues that rose out these events are used to interpret whether the state of globalization is influenced. The issues of economic class, unemployment, CEO compensation, The Kyoto Protocol, the rise of social media, and Saudi Arabia’s joining the WTO are examined based on their influence on the state of globalization. The study concludes that convergence of cultures, based on nation-states’ responses to the arbitrage of information in the areas of economies, politics, environment, law, culture, and ethics has is a real influence on the state of globalization. The negative or positive effects of globalization are irrelevant in comparison to the actions taking by nation-states in response to key events.